MODELLING TRADE DURATIONS WITH THE BIRNBAUM-SAUNDERS AUTOREGRESSIVE MODEL - Mayorov, Kirill (My University, 2011)
In this thesis we study the Birnbaum-Saunders autoregressive conditional du- ration (BS-ACD) model. As opposed to the standard ACD model, formulated in terms of the conditional mean duration, the BS-ACD model specifies the time-varying model dynamics in terms of the conditional median duration. By means of Monte Carlo simulations, we examine the asymptotic behaviour of the maximum likelihood estimators. We then present a study of numerical efficacy of some optimization algorithms in relation to the BS-ACD model. On a practical side, we fit the BS-ACD model to samples for six securities listed on the New York Stock Exchange.
Keywords: high-frequency data; ACD model; Birnbaum-Saunders distribution; Statistics and Probability; Statistics and Probability